Adhesive composition and optical laminate with adhesive layer
By using an adhesive composition of an alkoxy group (meth)acrylic copolymer and a phthaldimethyldiisocyanate isocyanate crosslinking agent, the problem of insufficient durability and prone to yellowing in the prior art is solved, and the excellent performance of the thin film adhesive layer at high temperature is achieved.
Patent Information
- Application Number
- CN202380060488.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-08-25
- Filing Date
- 2023-07-11
- Publication Date
- 2025-03-28
AI Technical Summary
The prior art is difficult to prepare a thin film adhesive layer suitable for optical components while maintaining high temperature durability and preventing yellowing.
The adhesive composition containing 20% or more of alkoxy group (meth)acrylic monomers and an isocyanate-based crosslinking agent derived from a phthaldimethyldiisocyanate-based compound was used to ensure high-temperature durability and yellowing resistance of the adhesive layer.
It realizes the high-temperature durability of the adhesive layer and prevents yellowing or whitening under high temperature environments (such as 115°C), and is suitable for thin optical components.
Smart Images

Figure BDA0005275630500000251 
Figure BDA0005275630500000291
Abstract
Description
Technical Field
[0001] One embodiment of the present invention relates to an adhesive composition or an optical laminate with an adhesive layer. Background Art
[0002] In recent years, with the continuous development of lightweight and thinning of various objects, in order to solve the various problems caused by such lightweight and thinning of various components, further high functionality and high durability are required. For example, recently, a large number of thin and narrow-framed image display devices have been developed. At the same time, the optical film or adhesive layer constituting the optical component is required to be thinner.
[0003] The thickness of the adhesive layer formed on optical components such as polarizing plates used in image display devices is generally about 20 to 25 μm. However, if the adhesive layer of such optical components is made thinner, the polarizing plates may be easily deformed during thermal shrinkage, causing stress on the adhesive layer to be concentrated locally, resulting in poor adhesion such as peeling or foaming.
[0004] As compositions for solving such problems and producing adhesive layers having high durability, adhesive compositions containing an excess amount of isocyanate compounds relative to the amount of crosslinking points possessed by acrylic polymers are proposed in Patent Documents 1 and 2. It is speculated that in the inventions described in these publications, the reaction products of the isocyanate compounds that do not participate in crosslinking improve the adhesive properties such as durability of the adhesive layer. Prior art literature Patent Literature
[0005] Patent Document 1: Japanese Patent Application Publication No. 2010-196003 Patent Document 2: Japanese Patent Application Publication No. 2010-159346 Summary of the invention
[0006] The isocyanate compounds actually used in Patent Documents 1 and 2 are all toluene diisocyanate (TDI) compounds. However, when toluene diisocyanate compounds are used, discoloration (yellowing) over time is known, and yellowing is known to be a problem depending on the application. Also, diphenylmethane diisocyanate (MDI) compounds are known as crosslinking agents used in conventional adhesive compositions. However, such MDI compounds are also known to be susceptible to yellowing, similar to toluene diisocyanate compounds, depending on the usage environment. That is, it is found that it is difficult to achieve both high-temperature durability and suppression of yellowing in conventional adhesive compositions.
[0007] As isocyanate compounds that are less likely to cause yellowing, hexamethylene diisocyanate (HDI) compounds are known. However, it is known that the reaction products obtained from hexamethylene diisocyanate compounds are relatively soft, so even if an excessive amount of hexamethylene diisocyanate compounds is added, the high-temperature durability of the resulting adhesive composition is not sufficient depending on the application.
[0008] One embodiment of the present invention provides an adhesive composition, particularly an optical adhesive composition suitable for optical components, and an optical laminate with an adhesive layer. The adhesive composition can form an adhesive layer that is excellent in high temperature durability and is not prone to yellowing or whitening despite being a thin film. Solutions to technical problems
[0009] The present inventors have conducted research and found that the above-mentioned technical problems can be solved according to the following configuration examples. The configuration examples of the present invention are as follows.
[0010] [1] An adhesive composition comprising a (meth)acrylic acid copolymer and an isocyanate crosslinking agent, The (meth)acrylic copolymer is a copolymer of a monomer mixture containing 20% by mass or more of a (meth)acrylic monomer having an alkylene oxide group. The isocyanate crosslinking agent has 3 or more isocyanate groups derived from a xylylene diisocyanate compound, and the content of the isocyanate crosslinking agent is greater than 2 parts by mass and less than 30 parts by mass based on 100 parts by mass of the (meth)acrylic copolymer.
[0011] [2] The adhesive composition according to [1], wherein the (meth)acrylic copolymer is a copolymer of a monomer mixture containing 50% by mass or more of a (meth)acrylic monomer having an alkylene group.
[0012] [3] The adhesive composition according to [1] or [2], wherein the content of the structural unit derived from the acidic group-containing monomer in the (meth)acrylic copolymer is less than 1% by mass.
[0013] [4] The adhesive composition according to any one of [1] to [3], wherein the isocyanate crosslinking agent is an isocyanurate.
[0014] [5] The adhesive composition according to any one of [1] to [4], wherein the (meth)acrylic copolymer has a molecular weight distribution Mw / Mn, which is a ratio of a polystyrene-equivalent weight average molecular weight Mw to a number average molecular weight Mn as measured by gel permeation chromatography, of greater than 3.
[0015] [6] The adhesive composition according to any one of [1] to [5], which is used for an optical component.
[0016] [7] An optical laminate with an adhesive layer, comprising an adhesive layer formed from the adhesive composition according to any one of [1] to [6] and an optical film.
[0017] [8] An optical laminate with an adhesive layer, comprising an adhesive layer formed from the adhesive composition according to any one of [1] to [6] and an optical film, The adhesive layer has a thickness of 20 μm or less.
[0018] [9] An optical laminate with an adhesive layer, comprising an adhesive layer formed from the adhesive composition according to any one of [1] to [6] and an optical film, The adhesive layer has a yellowing value ΔYI, which is a difference in yellowness calculated in accordance with JIS K7373:2006, of 2.0 or less before and after being left to stand in an environment of 115° C. for 500 hours. Effects of the Invention
[0019] According to one embodiment of the present invention, an adhesive composition is provided, in particular, an optical adhesive composition applicable to optical components, especially optical components of image display devices, wherein the adhesive composition can form an adhesive layer that is thin but has excellent durability at high temperatures (e.g., 115° C.) and is not prone to yellowing or whitening. In addition, according to another embodiment of the present invention, an optical laminate with an adhesive layer formed from the optical adhesive composition is provided. DETAILED DESCRIPTION
[0020] 《Adhesive composition》 An adhesive composition according to one embodiment of the present invention (hereinafter also referred to as the "present composition") comprises a (meth)acrylic copolymer, which is a copolymer of a monomer mixture containing 20% by mass or more of a (meth)acrylic monomer having an alkylene oxide group (hereinafter also referred to as the "copolymer (a)"), and an isocyanate crosslinking agent, which is an isocyanate crosslinking agent having three or more isocyanate groups and is derived from a xylylenediisocyanate compound (hereinafter also referred to as the "isocyanate crosslinking agent (b)").
[0021] In this specification, a "(meth)acrylic copolymer" is a copolymer obtained using a polymerizable monomer containing at least a (meth)acrylic acid ester. In this specification, (meth)acrylic acid is used as a general term for acrylic acid and methacrylic acid, and may be either acrylic acid or methacrylic acid. (Meth)acrylate is used as a general term for acrylate and methacrylate, and may be either acrylate or methacrylate. In addition, (meth)acryloyl is used as a general term for acryloyl and methacryloyl, and may be either acryloyl or methacryloyl.
[0022] [Copolymer (a)] The copolymer (a) is a copolymer of a monomer mixture containing 20% by mass or more of a (meth)acrylic monomer having an alkylene group. The copolymer (a) used in the present composition may be one kind or two or more kinds.
[0023] The high-temperature durability of the adhesive layer is considered to be a property that is exerted by having a comprehensive influence on the adhesive properties such as the adhesion of the adherend in addition to the cohesive force. It is generally believed that if the adhesive layer has a certain thickness, the stress generated by the deformation of the adherend such as thermal shrinkage is dispersed in the adhesive layer, and the high-temperature durability can be exerted. However, reducing the thickness of the adhesive layer will lead to less room for stress dispersion in the adhesive layer, so the proportion of the influence on the adhesion of the adherend becomes higher. The copolymer (a) is a copolymer obtained by using 20% by mass or more of a (meth)acrylic monomer having an alkylene oxide group, and thus is a copolymer having a high polarity. Therefore, it is believed that the copolymer (a) has good adhesion to polar adherends such as glass, and by using the copolymer (a), excellent high temperature durability can be exhibited even when the film thickness is reduced.
[0024] In addition, the copolymer (a) is a copolymer with a high polarity, and thus has excellent compatibility with the isocyanate crosslinking agent (b). Therefore, in the present composition containing the copolymer (a), even if the isocyanate crosslinking agent (b) is blended, whitening caused by phase separation of the copolymer (a) and the isocyanate crosslinking agent (b) is not likely to occur. In addition, the isocyanate crosslinking agent (b) is an isocyanate compound that is not likely to cause yellowing, so the present composition is not likely to cause whitening or yellowing.
[0025] [(Meth)acrylic monomer having an alkylene oxide group] The copolymer (a) contains 20% by mass or more of a structural unit derived from a (meth)acrylic monomer having an alkyleneoxy group, when the total mass of the copolymer (a) is taken as 100% by mass. Here, alkyleneoxy (oxyalkylene) refers to a group represented by -RO- (R is an alkylene group). In addition, since -RO- in -R-OH is generally not called an alkyleneoxy group, a monomer other than -R-OH that does not have -RO- is not a (meth)acrylic monomer having an alkyleneoxy group. The (meth)acrylic monomer having an alkylene oxide group used in the monomer mixture may be one kind or two or more kinds.
[0026] From the viewpoint of further exhibiting the effects of the present invention, the (meth)acrylic monomer having an alkyleneoxy group preferably does not have a functional group (for example, a crosslinkable functional group described below) that can react with a crosslinking agent to form a crosslink.
[0027] The (meth)acrylic monomer having an alkyleneoxy group is represented by, for example, formula (1). CH2=CR 1 -COOR 2 …(1) R 1 is a hydrogen atom or a methyl group, R 2 It is a group represented by formula (2). -(R 3 O) n R 4 ···(2) R 3 is an alkylene group, R 4 is a hydrocarbon group having 1 to 12 carbon atoms, and n is an integer greater than 1. The number of carbon atoms in the alkylene group is usually 1 to 10, preferably 1 to 5. The number of carbon atoms in the hydrocarbon group is preferably 1 to 10, more preferably 1 to 6, and further preferably 1 to 4. n is preferably 1 to 20, more preferably 1 to 10, and further preferably 1 to 4.
[0028] As a (meth)acrylic-type monomer which has an alkylene group, an alkoxyalkyl (meth)acrylate and the (meth)acrylic monomer which has a polyoxyalkylene group are mentioned, for example. Examples of the alkoxyalkyl (meth)acrylate include methoxymethyl (meth)acrylate, 2-methoxyethyl (meth)acrylate, 2-ethoxyethyl (meth)acrylate, 3-methoxypropyl (meth)acrylate, 3-ethoxypropyl (meth)acrylate, 4-methoxybutyl (meth)acrylate, and 4-ethoxybutyl (meth)acrylate. Specific examples of the (meth)acrylic monomer having a polyoxyalkylene group include: methoxypolyethylene glycol (meth)acrylates such as methoxydiethylene glycol (meth)acrylate and methoxytriethylene glycol (meth)acrylate; ethoxypolyethylene glycol (meth)acrylates such as ethoxydiethylene glycol (meth)acrylate and ethoxytriethylene glycol (meth)acrylate; butoxypolyethylene glycol (meth)acrylates such as butoxydiethylene glycol (meth)acrylate and butoxytriethylene glycol (meth)acrylate; phenoxypolyethylene glycol (meth)acrylates such as phenoxydiethylene glycol (meth)acrylate and phenoxytriethylene glycol (meth)acrylate; and methoxypolypropylene glycol (meth)acrylates such as methoxydipropylene glycol (meth)acrylate.
[0029] Among the (meth)acrylic monomers having an alkyleneoxy group, ethoxydiethylene glycol acrylate, methoxytriethylene glycol acrylate, and 2-methoxyethyl acrylate are preferred, and methoxytriethylene glycol acrylate and 2-methoxyethyl acrylate are particularly preferred.
[0030] In the monomer mixture, which is the raw material of the copolymer (a), the content of the (meth) acrylic monomer having an alkylene oxide group is 20% by mass or more, preferably 50% by mass or more, more preferably 70% by mass or more, further preferably 90% by mass or more, preferably 100% by mass or less, more preferably 99.99% by mass or less. In the case where the monomer mixture contains the following other monomers, the upper limit of the content of the (meth) acrylic monomer having an alkylene oxide group in the monomer mixture may be 98.99% by mass. When the content of the (meth) acrylic monomer having an alkyleneoxy group in the monomer mixture is within the above range, the polarity of the copolymer (a) can be increased. As a result, even if an excessive amount of the isocyanate crosslinking agent (b) is added, whitening caused by phase separation of the copolymer (a) and the isocyanate crosslinking agent (b) is not likely to occur. In addition, when the content of the (meth) acrylic monomer having an alkyleneoxy group in the monomer mixture is within the above range, an adhesive layer showing good adhesion to an adherend, especially to a polar adherend, can be easily obtained, so that even if the film thickness of the adhesive layer is reduced, excellent high-temperature durability can be obtained.
[0031] [Monomer containing a cross-linkable functional group] The copolymer (a) may include a structural unit derived from a monomer containing a crosslinkable functional group. The monomer containing a crosslinkable functional group is preferably a (meth)acrylic compound having a crosslinkable functional group. The "crosslinkable functional group" in the crosslinkable functional group-containing monomer refers to a functional group that can react with a crosslinking agent to form a crosslink. Examples of the crosslinkable functional group include acidic groups such as a carboxyl group and a carbonyl group, a hydroxyl group, an amino group, an amide group, an epoxy group and a cyano group. Among them, a hydroxyl group, an amino group and a carboxyl group are preferred.
[0032] When the above-mentioned monomer containing a cross-linkable functional group is used, the content of the monomer containing a cross-linkable functional group in the raw material of the above-mentioned copolymer (a), i.e., the above-mentioned monomer mixture, is preferably 0.001 to 10% by mass, more preferably 0.005 to 7% by mass, and further preferably 0.01 to 4% by mass, from the perspective of appropriately forming the cross-linked structure of the above-mentioned copolymer (a) and obtaining an adhesive layer with moderate cohesive force.
[0033] (Hydroxy-containing monomers) The copolymer (a) may contain at least one structural unit derived from a hydroxyl group-containing monomer. Examples of the hydroxyl-containing monomer include 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 3-hydroxypropyl (meth)acrylate, 4-hydroxybutyl (meth)acrylate, 6-hydroxyhexyl (meth)acrylate, 8-hydroxyoctyl (meth)acrylate, 10-hydroxydecyl (meth)acrylate, 12-hydroxylauryl (meth)acrylate, and (4-hydroxymethylcyclohexyl)methyl (meth)acrylate. The hydroxyl group-containing monomer may be used alone or in combination of two or more.
[0034] When a hydroxyl-containing monomer is used, the content of the hydroxyl-containing monomer in the above-mentioned monomer mixture is preferably 0.005 to 7% by mass, more preferably 0.01 to 4% by mass, from the perspectives that the resulting adhesive layer can easily form a layer with a moderate crosslinking density, has excellent stress relaxation properties, and is not easily peeled from the adherend.
[0035] (Amino-containing monomers) The copolymer (a) may contain at least one structural unit derived from an amino group-containing monomer. As said amino group-containing monomer, dialkylaminoalkyl (meth)acrylates, such as dimethylaminoethyl (meth)acrylate and diethylaminoethyl (meth)acrylate, are mentioned, for example. The amino group-containing monomer may be used alone or in combination of two or more. In addition, an amide group or an imide group is generally not included in an amino group, and therefore, in the present specification, a monomer having an amide group or an imide group but not having an amino group other than the amide group or the imide group is not an amino group-containing monomer.
[0036] When an amino-containing monomer is used, the content of the amino-containing monomer in the above-mentioned monomer mixture is preferably 0.005 to 7% by mass, more preferably 0.01 to 4% by mass, from the perspectives that the resulting adhesive layer can easily form a layer with a moderate crosslinking density, has excellent stress relaxation properties, and is not easily peeled from the adherend.
[0037] (monomer containing acidic group) The copolymer (a) may contain at least one structural unit derived from an acidic group-containing monomer. Examples of the acidic group-containing monomer include carboxyl group-containing monomers such as acrylic acid, methacrylic acid, β-carboxyethyl (meth)acrylate, 5-carboxypentyl (meth)acrylate, succinic acid mono(meth)acryloyloxyethyl ester, ω-carboxypolycaprolactone mono(meth)acrylate, crotonic acid, maleic acid, fumaric acid, itaconic acid, and citraconic acid. The acidic group-containing monomer may be used alone or in combination of two or more.
[0038] When using a monomer containing an acidic group, the content of the monomer containing an acidic group in the above-mentioned monomer mixture is preferably 0.005 to 7% by mass, more preferably 0.01 to 4% by mass, from the perspectives that the resulting adhesive layer can easily form a layer having a moderate crosslinking density, has excellent stress relaxation properties, and is not easily peeled from the adherend. However, in one embodiment of the present invention, when the corrosion caused by the acid component of the adherend in contact with the adhesive layer becomes a problem, for example, when the adhesive layer formed by the present composition is in direct contact with an adherend that is easily corroded by the acid component, such as a metal oxide layer such as ITO (indium tin composite oxide) or a conductive layer of a metal mesh containing metal (thin) wires formed into a lattice pattern, the content of the structural unit derived from the monomer containing an acid group in the copolymer (a) is preferably less than 1% by mass, more preferably 0.2% by mass or less, and more preferably 0.15% by mass or less, from the perspective of being able to easily suppress corrosion, etc. It is also preferred that the monomer mixture does not use a monomer containing an acid group.
[0039] (Other monomers containing cross-linking functional groups) Examples of monomers containing crosslinkable functional groups other than the above monomers include (meth)acrylamide; N-alkyl (meth)acrylamide such as N-(meth)acrylamide, N-ethyl (meth)acrylamide, N-propyl (meth)acrylamide, and N-hexyl (meth)acrylamide; N,N-dialkyl (meth)acrylamide such as N,N-dimethyl (meth)acrylamide and N,N-diethyl (meth)acrylamide; amide group-containing monomers such as cyclic amide group-containing monomers such as N-vinylpyrrolidone, N-vinylcaprolactam, and (meth)acryloylmorpholine; Nitrogen-containing heterocyclic monomers such as N-cyclohexylmaleimide, N-phenylmaleimide, N-lauroylmaleimide, and N-benzylmaleimide; Cyano-containing monomers such as acrylonitrile and methacrylonitrile.
[0040] [Other monomers that may be contained in the monomer mixture] The monomer mixture as a raw material of the copolymer (a) may contain other monomers in addition to the (meth)acrylic monomer having an alkyleneoxy group and the monomer containing a crosslinkable functional group. The other monomers may be used alone or in combination of two or more.
[0041] When the other monomer is used, the content of the other monomer in the monomer mixture as a raw material of the copolymer (a) is preferably greater than 0% by mass and not more than 50% by mass, more preferably 1 to 35% by mass.
[0042] Examples of the other monomers include alkyl (meth)acrylates having 1 to 20 carbon atoms, such as methyl (meth)acrylate, ethyl (meth)acrylate, n-propyl (meth)acrylate, isopropyl (meth)acrylate, n-butyl (meth)acrylate, isobutyl (meth)acrylate, tert-butyl (meth)acrylate, pentyl (meth)acrylate, hexyl (meth)acrylate, heptyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, n-octyl (meth)acrylate, isooctyl (meth)acrylate, nonyl (meth)acrylate, isononyl (meth)acrylate, decyl (meth)acrylate, isodecyl (meth)acrylate, undecyl (meth)acrylate, lauryl (meth)acrylate, oleyl (meth)acrylate, n-stearyl (meth)acrylate, and isostearyl (meth)acrylate. (Meth)acrylates containing an alicyclic hydrocarbon group, such as cyclohexyl (meth)acrylate, 4-tert-butylcyclohexyl (meth)acrylate, isobornyl (meth)acrylate, and adamantyl (meth)acrylate; (Meth)acrylates containing aromatic hydrocarbon groups such as benzyl (meth)acrylate, phenyl (meth)acrylate, and phenoxyethyl (meth)acrylate; Styrene monomers such as styrene, α-methylstyrene, p-methylstyrene, p-chlorostyrene, p-chloromethylstyrene, p-methoxystyrene, p-tert-butoxystyrene, divinylbenzene, indene, etc.; Vinyl ester compounds such as vinyl acetate, vinyl propionate, vinyl butyrate, vinyl caproate, vinyl benzoate, and vinyl cinnamate.
[0043] When the copolymer (a) contains a structural unit derived from an alkyl (meth)acrylate, the adhesive force and durability of the resulting adhesive layer tend to be easily adjustable. As the alkyl (meth)acrylate, from the viewpoint of further exerting the above-mentioned effects, alkyl (meth)acrylates having 1 to 8 carbon atoms are preferred, and alkyl (meth)acrylates having 1 to 4 carbon atoms are more preferred. When an alkyl (meth)acrylate is used, the content of the alkyl (meth)acrylate in the monomer mixture is preferably greater than 0 mass % and not more than 50 mass %, more preferably 1 to 35 mass %, from the viewpoint of more effectively exerting the above-mentioned effects.
[0044] When the copolymer (a) contains a structural unit derived from an alicyclic hydrocarbon group-containing (meth)acrylate, there is a tendency that the cohesive force and stress relaxation properties of the resulting adhesive layer can be easily adjusted. When an alicyclic hydrocarbon group-containing (meth)acrylate is used, the content of the alicyclic hydrocarbon group-containing (meth)acrylate in the monomer mixture is preferably greater than 0 mass % and 10 mass % or less, more preferably 1 to 5 mass %, from the viewpoint of further exerting the above-mentioned effects.
[0045] By making the copolymer (a) contain a structural unit derived from an aromatic hydrocarbon group-containing (meth)acrylate, there is a tendency to easily form an adhesive layer having better adhesion to the adherend. In the case of using an aromatic hydrocarbon group-containing (meth)acrylate, from the perspective of further exerting the above-mentioned effect, the content of the aromatic hydrocarbon group-containing (meth)acrylate in the above-mentioned monomer mixture is preferably greater than 0% by mass and less than 10% by mass, and more preferably 1 to 5% by mass.
[0046] When the styrene monomers and vinyl ester compounds are used, the content of these monomers and compounds in the monomer mixture is not particularly limited, but is preferably greater than 0% by mass and less than 10% by mass, and more preferably 1 to 5% by mass.
[0047] [Method for synthesizing copolymer (a)] The copolymer (a) can be synthesized by polymerizing the monomers in the above-mentioned monomer mixture, for example, it can be a random polymer, a block polymer or a graft polymer, and can be synthesized by various polymerization methods. The polymerization method is not particularly limited, for example, solution polymerization, bulk polymerization, emulsion polymerization, suspension polymerization can be exemplified. Among them, from the aspects that the processing steps when manufacturing the present composition are relatively simple and can be carried out in a short time, etc., it is preferably polymerized by solution polymerization.
[0048] As a specific example of solution polymerization, the following method can be cited: add a monomer mixture, a polymerization initiator, and other components such as a chain transfer agent and a polymerization solvent used as needed into a reaction container, set the reaction starting temperature to usually 40 to 100° C., preferably 50 to 80° C., maintain the reaction system at a temperature of usually 50 to 90° C., preferably 60 to 90° C., and react the reaction system for 2 to 20 hours. The reaction is carried out, for example, under an inert gas atmosphere such as nitrogen. In addition, in the polymerization reaction, at least one selected from a monomer mixture, a polymerization initiator, a chain transfer agent, and a polymerization solvent can be added.
[0049] As a polymerization initiator, an azo type initiator and a peroxide type polymerization initiator are mentioned, for example. Examples of the azo initiator include 2,2'-azobisisobutyronitrile, 2,2'-azobis(4-methoxy-2,4-dimethylvaleronitrile), 2,2'-azobis(2-cyclopropylpropionitrile), 2,2'-azobis(2,4-dimethylvaleronitrile), 2,2'-azobis(2-methylbutyronitrile), 1,1'-azobis(cyclohexane-1-carbonitrile), 2-(carbamoylazo)isobutyronitrile, 2-phenylazo-4-methoxy-2,4-dimethylvaleronitrile, 2,2'-azobis( azo compounds such as 2,2'-azobis(2-amidinopropane) dihydrochloride, 2,2'-azobis(N,N'-dimethylisobutylamidine), 2,2'-azobis[2-methyl-N-(2-hydroxyethyl)-propionamide], 2,2'-azobis(isobutylamide) dihydrate, 4,4'-azobis(4-cyanovaleric acid), 2,2'-azobis(2-cyanopropanol), dimethyl-2,2'-azobis(2-methylpropionate), and 2,2'-azobis(2-methyl-N-(2-hydroxyethyl)propionamide).
[0050] Examples of the peroxide polymerization initiator include tert-butyl hydroperoxide, cumene hydroperoxide, diisopropylbenzene hydroperoxide, benzoyl peroxide, lauroyl peroxide, hexanoyl peroxide, diisopropyl peroxydicarbonate, di-2-ethylhexyl peroxydicarbonate, tert-butyl peroxypivalate, 2,2-bis(4,4-di-tert-butylperoxycyclohexyl)propane, 2,2-bis(4,4-di-tert-amylperoxycyclohexyl)propane, 2,2-bis(4,4-di-tert-octylperoxycyclohexyl)propane, 2,2-bis(4,4-di-α-isopropylphenylperoxycyclohexyl)propane, 2,2-bis(4,4-di-tert-butylperoxycyclohexyl)butane, and 2,2-bis(4,4-di-tert-octylperoxycyclohexyl)butane.
[0051] The above-mentioned polymerization initiator may be used alone or in combination of two or more. In addition, the polymerization initiator may be added multiple times during the polymerization. The amount of the polymerization initiator used is usually 0.001 to 5 parts by mass, preferably 0.005 to 3 parts by mass, based on 100 parts by mass of the monomer mixture.
[0052] Examples of the polymerization solvent used in the solution polymerization include aromatic hydrocarbons such as benzene, toluene, and xylene; aliphatic hydrocarbons such as n-pentane, n-hexane, n-heptane, and n-octane; alicyclic hydrocarbons such as cyclopentane, cyclohexane, cycloheptane, and cyclooctane; ethers such as diethyl ether, diisopropyl ether, 1,2-dimethoxyethane, dibutyl ether, tetrahydrofuran, dioxane, anisole, phenethyl ether, and diphenyl ether; halogenated hydrocarbons such as chloroform, carbon tetrachloride, 1,2-dichloroethane, and chlorobenzene; esters such as methyl acetate, ethyl acetate, propyl acetate, butyl acetate, and methyl propionate; ketones such as acetone, methyl ethyl ketone, diethyl ketone, methyl isobutyl ketone, and cyclohexanone; amides such as N,N-dimethylformamide, N,N-dimethylacetamide, and N-methylpyrrolidone; nitriles such as acetonitrile and benzonitrile; and sulfoxides such as dimethyl sulfoxide and cyclopentane. The above-mentioned polymerization solvents may be used alone or in combination of two or more.
[0053] [Physical Properties of Copolymer (a)] The weight average molecular weight (Mw) of the copolymer (a) in terms of polystyrene measured by gel permeation chromatography (GPC) is preferably 900,000 to 2,000,000, more preferably 1,200,000 to 2,000,000, and even more preferably 1,500,000 to 2,000,000. When Mw is within the above range, there is a tendency that an adhesive layer having excellent durability and cohesive force can be easily formed. Specifically, the Mw can be measured by the method described in the following Examples.
[0054] The ratio of the weight average molecular weight (Mw) to the number average molecular weight (Mn) in terms of polystyrene measured by gel permeation chromatography (GPC) of the copolymer (a), i.e., the molecular weight distribution (Mw / Mn) is preferably greater than 3, more preferably greater than 3 and not more than 20, and further preferably greater than 3 and not more than 10. When the molecular weight distribution (Mw / Mn) is within the above range, an adhesive layer having excellent adhesion to an adherend and stress relaxation properties tends to be easily formed. Specifically, the Mw / Mn can be measured by the method described in the following Examples.
[0055] [Content of copolymer (a)] The content of the copolymer (a) in the present composition is preferably 50 to 98% by mass, more preferably 60 to 94% by mass, and even more preferably 60 to 91% by mass, based on 100% by mass of the nonvolatile components of the present composition. When the content of the copolymer (a) is within the above range, an adhesive layer having good adhesion to an adherend, particularly a polar adherend, and excellent high-temperature durability in spite of being a thin film can be easily formed.
[0056] [Isocyanate crosslinking agent (b)] The isocyanate-based crosslinking agent (b) is an isocyanate-based crosslinking agent having three or more isocyanate groups and derived from a xylylenediisocyanate-based compound. The isocyanate crosslinking agent (b) used in the present composition may be one kind or two or more kinds.
[0057] Since such an isocyanate crosslinking agent (b) is not easy to cause yellowing and has good compatibility with the copolymer (a), it is not easy to cause whitening. In addition, since the isocyanate crosslinking agent (b) has a relatively rigid property, by using the isocyanate crosslinking agent (b), the resulting adhesive layer has high cohesion even in a high temperature environment and excellent high temperature durability.
[0058] The number of isocyanate groups in one molecule of the isocyanate crosslinking agent (b) is preferably 3 to 8, more preferably 3 to 6. The number of isocyanate groups within the above range is preferred from the perspective of the crosslinking reaction efficiency between the copolymer (a) and the isocyanate crosslinking agent (b) and the perspective of maintaining the flexibility of the resulting adhesive layer.
[0059] As isocyanate crosslinking agents (b), for example, there can be mentioned: polymers (e.g., trimers, isocyanurates), derivatives (e.g., addition reaction products with polyols), and polymers of xylylene diisocyanate or hydrogenated xylylene diisocyanate. As polyols in the above derivatives, low molecular weight polyols can be trivalent or higher alcohols such as trimethylolpropane, glycerol, and pentaerythritol; high molecular weight polyols can be polyether polyols, polyester polyols, acrylic polyols, polybutadiene polyols, and polyisoprene polyols.
[0060] Specific examples of the isocyanate crosslinking agent (b) include trimers of xylylenediisocyanate, isocyanurates of xylylenediisocyanate, and reaction products of trimethylolpropane and xylylenediisocyanate (eg trimolecular adducts of xylylenediisocyanate).
[0061] [Content of isocyanate crosslinking agent (b)] The content of the isocyanate crosslinking agent (b) in the present composition is more than 2 parts by mass and less than 30 parts by mass, preferably 5 to 25 parts by mass, and more preferably 8 to 20 parts by mass, based on 100 parts by mass of the copolymer (a). When the content of the isocyanate crosslinking agent (b) in the present composition is within the above range, even when a thin film adhesive layer is produced from the present composition, the adhesive layer has excellent high temperature durability and is less likely to yellow or whiten. When the content of the isocyanate crosslinking agent (b) exceeds the above range, the resulting adhesive layer tends to whiten easily.
[0062] [Other ingredients] The present composition may further comprise other ingredients other than the above-mentioned copolymer (a) and the isocyanate crosslinking agent (b), such as a silane coupling agent, a polymer other than the above-mentioned copolymer (a), a crosslinking agent other than the above-mentioned isocyanate crosslinking agent (b) (e.g., isocyanate compounds, epoxy compounds, metal chelates), an antistatic agent, a tackifying resin, an antioxidant, a light stabilizer, a metal corrosion inhibitor, a plasticizer, a crosslinking accelerator, a reprocessing agent, and an organic solvent, within the scope of not impairing the effects of the present invention. These other components may be used alone or in combination of two or more.
[0063] [Silane coupling agent] The present composition may contain a silane coupling agent. When the present composition contains a silane coupling agent, there is a tendency that an adhesive layer having high adhesive strength to an adherend can be easily formed. The above-mentioned silane coupling agents may be used alone or in combination of two or more.
[0064] Examples of the silane coupling agent include: silicon compounds containing polymerizable unsaturated groups such as vinyltrimethoxysilane, vinyltriethoxysilane, and methacryloxypropyltrimethoxysilane; epoxy group-containing silane coupling agents such as 3-glycidoxypropyltrimethoxysilane, 3-glycidoxypropyltriethoxysilane, 3-glycidoxypropylmethyldimethoxysilane, 3-glycidoxypropylmethyldiethoxysilane, and 2-(3,4-epoxycyclohexyl)ethyltrimethoxysilane; amino group-containing silane coupling agents such as 3-aminopropyltrimethoxysilane, N-(2-aminoethyl)-3-aminopropyltrimethoxysilane, and N-(2-aminoethyl)-3-aminopropylmethyldimethoxysilane; and halogen-containing silane coupling agents such as 3-chloropropyltrimethoxysilane. Among them, epoxy group-containing silane coupling agents are preferred because they tend to be able to easily form an adhesive layer excellent in stress relaxation properties.
[0065] When the present composition contains a silane coupling agent, the content of the silane coupling agent is usually 1 part by mass or less, preferably 0.01 to 1 part by mass, and more preferably 0.05 to 0.5 parts by mass, based on 100 parts by mass of the copolymer (a). When the content of the silane coupling agent is within the above range, the adhesive layer can be easily prevented from being peeled off from the adherend even in a high temperature environment, and there is a tendency that an adhesive layer that is unlikely to bleed out of the silane coupling agent can be easily formed.
[0066] [Polymers other than copolymer (a)] The polymer other than the copolymer (a) (hereinafter also referred to as "polymer (c)") is not particularly limited, but is preferably a (meth)acrylic polymer. The polymer (c) may be a homopolymer or a copolymer. The polymer (c) may be used alone or in combination of two or more.
[0067] The polymer (c) (meth)acrylic polymer may be a (meth)acrylic polymer containing less than 20% by mass of a structural unit derived from a (meth)acrylic monomer having an alkylene group. The Mw of the polymer (c) (meth)acrylic polymer is not particularly limited, but is preferably 5,000 to 3,000,000, more preferably 10,000 to 2,000,000, and even more preferably 10,000 to 1,500,000.
[0068] The raw materials, i.e., monomers of the polymer (c) (meth)acrylic polymer may be the same monomers as those described in the above-mentioned copolymer (a), and the method for synthesizing the polymer (c) (meth)acrylic polymer may be the same method as that for synthesizing the above-mentioned copolymer (a).
[0069] When the present composition contains the polymer (c), the content of the polymer (c) is preferably 2 to 90 parts by mass, more preferably 5 to 50 parts by mass, based on 100 parts by mass of the copolymer (a). When the content of the copolymer (c) is within the above range, stress generated by shrinkage of optical components such as polarizing plates is easily relaxed, and an adhesive layer that is unlikely to peel from an adherend tends to be easily formed.
[0070] [Antistatic Agent] Examples of the antistatic agent include surfactants, ionic compounds and conductive polymers. The above antistatic agents may be used alone or in combination of two or more.
[0071] Examples of the surfactant include: cationic surfactants having cationic groups such as quaternary ammonium salts, amide quaternary ammonium salts, pyridinium salts, and primary to tertiary amino groups; anionic surfactants having anionic groups such as sulfonate groups, sulfate groups, and phosphate groups; amphoteric surfactants such as alkyl betaines, alkyl imidazolinium betaines, alkyl amine oxides, and amino acid sulfates; and nonionic surfactants such as glycerol fatty acid esters, sorbitan fatty acid esters, polyoxyethylene alkylamines, polyoxyethylene alkylamine fatty acid esters, N-hydroxyethyl-N-2-hydroxyalkylamines, and alkyl diethanolamides.
[0072] In addition, as the surfactant, a reactive emulsifier having a polymerizable group may be mentioned, and a polymer surfactant obtained by increasing the molecular weight of a monomer component including the above-mentioned surfactant or reactive emulsifier may be used.
[0073] An ionic compound is composed of a cation part and an anion part, and can be a solid compound or a liquid compound at room temperature (23° C.) and 50% RH (relative humidity).
[0074] The cation part constituting the ionic compound may be either an inorganic cation or an organic cation, or both. As the inorganic cation, alkali metal ions and alkaline earth metal ions are preferred, and Li ions having excellent antistatic properties are more preferred. + 、Na + and K + Examples of the organic cation include pyridinium cations, piperidinium cations, pyrrolidinium cations, pyrrolinium cations, pyrrole cations, imidazolium cations, tetrahydropyridinium cations, dihydropyridinium cations, pyrazolium cations, pyrazolinium cations, tetraalkylammonium cations, trialkylalkoxyammonium cations, trialkylsulfonium cations, tetraalkylphosphonium cations, and derivatives thereof.
[0075] The anion part constituting the ionic compound is not particularly limited as long as it can form an ionic compound by ion bonding with the cation part. - , Cl - Br - ,I - 、AlCl4 - 、Al2Cl7 - 、BF4 - PF6 - 、SCN - 、ClO4 - 、NO3 - 、CH3COO - CF3COO -、CH3SO3 - CF3SO3 - 、(CF3SO2)2N - 、(FSO2)2N - 、(CF3SO2)3C - 、AsF6 - 、SbF6 - 、NbF6 - 、TaF6 - 、F(HF) n - (n is 1 to 3), (CN)2N - 、C4F9SO3 - 、(C2F5SO2)2N - 、C3F7COO - and (CF3SO2)(CF3CO)N - .
[0076] Examples of the ionic compound include lithium bis(trifluoromethylsulfonyl)imide, lithium bis(fluorosulfonyl)imide, lithium tris(trifluoromethylsulfonyl)methane, potassium bis(trifluoromethylsulfonyl)imide, potassium bis(fluorosulfonyl)imide, 1-ethylpyridinium hexafluorophosphate, 1-butylpyridinium hexafluorophosphate, 1-hexyl-4-methylpyridinium hexafluorophosphate, 1-octyl-4-methylpyridinium hexafluorophosphate, 1-octyl-4-methylpyridinium bis(fluorosulfonyl)imide, 1-octyl-4-methylpyridinium bis(trifluoromethylsulfonyl)imide, N,N-diethyl-N-methyl-N-(2-methoxyethyl)ammonium tetrafluoroborate, N,N-diethyl-N-methyl-N-(2-methoxyethyl)ammonium bis(trifluoromethylsulfonyl)imide, 1-octylpyridinium fluorosulfonylimide, and 1-octyl-3-methylpyridinium trifluorosulfonylimide.
[0077] The conductive polymer may, for example, be polythiophene, polyaniline, polypyrrole or a derivative thereof.
[0078] When the present composition contains an antistatic agent, the content of the antistatic agent is preferably 3 parts by mass or less, more preferably 0.01 to 3 parts by mass, and further preferably 0.05 to 2.5 parts by mass, based on 100 parts by mass of the copolymer (a).
[0079] [Organic solvents] The composition of the present invention may contain an organic solvent within a range not impairing the effects of the present invention. The above-mentioned organic solvents may be used alone or in combination of two or more. Examples of the organic solvent include the same ones as the polymerization solvents described in the section of the synthesis method of the above copolymer (a). As the present composition containing such an organic solvent, for example, an organic solvent may be used when preparing the present composition, or a polymer solution containing the copolymer (a) and a polymerization solvent and an isocyanate-based crosslinking agent (b) may be used. The content of the organic solvent in the present composition is, for example, 0 to 90 mass %, or preferably 10 to 90 mass %.
[0080] <Method for producing the present composition> The present composition can be produced by mixing the copolymer (a), the isocyanate crosslinking agent (b), and the other components as required by a known method using a stirring device or the like. When the components are mixed and stirred, the components may be mixed and stirred all at once or sequentially. The stirring conditions are not particularly limited, but from the viewpoint of operability and productivity, stirring at room temperature for about 10 to 120 minutes may be sufficient.
[0081] <Use of the present composition> In order to exert the above-mentioned effects, the present composition is suitably used for optical parts, particularly optical parts of image display devices. Specific examples of the optical component include polarizing plates, and the present composition is particularly suitable for use in laminating components constituting display devices including polarizing plates. As the above-mentioned image display device, for example, a liquid crystal display or an organic EL display can be cited. Usually, the following optical laminate with the present adhesive layer is pasted on the image display unit (for example: liquid crystal cell, organic EL display unit) of the image display device, especially on the glass or resin substrate constituting the image display unit.
[0082] The parts (adherends) to which the present composition is attached include, for example, optical films such as polarizing films (including elliptical polarizing films, etc.), phase difference films, antireflection films, brightness enhancement films, light diffusion films, hard coatings, metal oxide layers such as metal or ITO layers, and glass or resin substrates.
[0083] <Adhesive Layer> The present composition is generally used as an adhesive layer formed of the present composition (hereinafter also referred to as "the present adhesive layer"). The present adhesive layer is formed from the present composition, and is preferably formed by subjecting the present composition to a cross-linking reaction. Thus, as an example of a preferred form of the present adhesive layer obtained by subjecting the present composition to a crosslinking reaction, there can be mentioned a form comprising a crosslinked product obtained by reacting the copolymer (a) with an isocyanate-based crosslinking agent (b), and there can also be mentioned a form in which the self-condensate of the remaining isocyanate-based crosslinking agent (b) participating in the crosslinking reaction is complexed with at least one selected from the copolymer (a) and a crosslinked product of the copolymer (a).
[0084] The thickness of the present adhesive layer can be appropriately set according to the purpose of the present adhesive layer, etc., and is not particularly limited, but is usually 5 to 100 μm, preferably 8 to 50 μm. Even if the thickness of the adhesive layer is reduced, it has good adhesion to the adherend and excellent high-temperature durability, and is therefore particularly suitable for lightweight and thin applications. From the perspective of further exerting the effects of the present invention, the thickness of the adhesive layer is preferably less than 20 μm, more preferably 5 to 20 μm, and further preferably 8 to 20 μm.
[0085] [Method for forming the adhesive layer] The adhesive layer can be formed on the adherend or support by, for example, applying the composition to the adherend or support and causing the applied composition to undergo a crosslinking reaction. After applying the composition to the adherend or support, the adherend or support can be further arranged on the applied surface as needed to cause the composition to undergo a crosslinking reaction.
[0086] When only the adhesive layer is to be formed, the adhesive layer may be peeled off from the support. The adhesive layer may be stored or moved together with the support during storage or transportation, and then peeled off from the support during use to use only the adhesive layer. As the support, a release-treated substrate may be mentioned.
[0087] When the present adhesive layer is used as a laminate with the adherend, for example, the present composition is applied to the adherend or support, and the support or adherend is further arranged on the applied surface, so that a laminate in which the present adhesive layer and the support are sequentially laminated can be obtained. When the laminate is used, the support can be peeled off and the laminate can be used as a laminate consisting of the adherend and the present adhesive layer.
[0088] The substrate of the adherend or the substrate used as the support is not particularly limited, and examples thereof include resin plates, glass plates, woven fabrics, nonwoven fabrics, and paper. The resin is preferably a transparent resin, and examples of the transparent resin include polycarbonate (PC), polymethyl methacrylate (PMMA), polyethylene terephthalate (PET), polypropylene (PP), acrylonitrile-butadiene-styrene copolymer (ABS), and polyamide (nylon).
[0089] The coating method of the present composition may be a known method, for example, a method of coating the obtained adhesive layer to a predetermined thickness by spin coating, blade coating, roll coating, bar coating, knife coating, die coating or gravure coating. In addition, depending on the situation, the present composition may be placed on the adherend or support by immersing the adherend or support in the present composition instead of applying the composition.
[0090] After applying the present composition to an adherend or a support, the applied present composition may be dried as required. The drying conditions vary depending on the type of solvent, but examples thereof include drying at 50 to 150° C., preferably 60 to 100° C., for usually 1 to 10 minutes, preferably 2 to 7 minutes.
[0091] It is preferred that a step of curing the present composition be provided after drying the applied present composition as required. The curing conditions include curing for usually 3 days or more, preferably 7 to 10 days, under an environment of usually 5 to 60°C, preferably 15 to 40°C, and usually 5 to 70% RH, preferably 5 to 50% RH. Curing under such conditions tends to allow sufficient crosslinking and facilitates formation of an adhesive layer with stable physical properties.
[0092] [Physical properties of this adhesive layer] 〔Yellowness value〕 The difference in yellowness before and after the adhesive layer is left standing for 500 hours at 115°C, i.e., the yellowing value ΔYI, is preferably less than 2.0, more preferably less than 1.8, and further preferably less than 1.5. In addition, the yellowing value ΔYI is the difference (YI-YI0) between the yellowness (YI0) of the adhesive layer before being placed at 115°C and the yellowness (YI) of the adhesive layer after being left standing for 500 hours at 115°C. Here, both the yellowness (YI0) and the yellowness (YI) are obtained in accordance with JIS K 7373:2006. In addition, in the following description, the yellowness YI of the adhesive layer after being left standing for 500 hours at 115°C is sometimes described as "the yellowness YI of the adhesive layer after high temperature durability". When the yellowing value ΔYI of the adhesive layer is within the above range, the yellowing of the adhesive layer has little influence on the image display device using the adhesive layer, etc. In addition, when the adhesive layer is laminated with an optical film to form an optical laminate with an adhesive layer described later, the influence of the yellowing of the adhesive layer is also small. The yellowness index YI of the adhesive layer after high-temperature durability (115° C., standing for 500 hours) is preferably 10.0 or less, more preferably 8.0 or less, and even more preferably 5.0 or less. If the yellowness YI of the adhesive layer after high temperature durability is within the above range, the adhesive layer is suitable for optical applications such as image display devices. In addition, the adhesive layer is suitable for laminating an optical laminate with an adhesive layer described below.
[0093] (Gel fraction) The gel fraction of the adhesive layer measured by the method described in the examples described below is preferably 30 to 99%, more preferably 45 to 98%, and further preferably 60 to 97%. When the gel fraction of the adhesive layer is within the above range, the adhesive layer has excellent stress relaxation properties and is difficult to peel from the adherend, and particularly has a tendency to be an adhesive layer with excellent high temperature durability.
[0094] 〔Adhesion〕 The adhesive strength of the adhesive layer measured by the method described in the examples described below is preferably 1 N / 25 mm or more, more preferably 2 N / 25 mm or more, and further preferably 3 N / 25 mm or more. The upper limit of the adhesive strength of the adhesive layer is not particularly limited, but is preferably 100 N / 25 mm or less, more preferably 75 N / 25 mm or less, and further preferably 50 N / 25 mm or less. When the adhesive force of the present adhesive layer is within the above range, the present adhesive layer is excellent in workability and adhesiveness.
[0095] "Optical laminate with adhesive layer" Examples of the optical laminate with an adhesive layer (hereinafter also referred to as “optical laminate with the present adhesive layer”) according to one embodiment of the present invention include a laminate including the present adhesive layer and a conventionally known optical film. The adhesive layer included in the optical laminate with adhesive layer can be 1 layer or more than 2 layers. In addition, the optical film included in the optical laminate with adhesive layer can be 1 sheet or more than 2 sheets. In the case of including more than 2 layers of adhesive layer, these layers can be the same layer or different layers. In addition, in the case of including more than 2 sheets of optical film, these films can be the same film or different films.
[0096] Examples of the optical film include a polarizing film (including an elliptical polarizing film), a phase difference film, an antireflection film, a brightness enhancement film, a light diffusion film, and a hard coat film. The thickness of the optical film is not particularly limited, but is usually 10 to 300 μm, preferably 15 to 250 μm, and more preferably 20 to 200 μm.
[0097] [Method for producing the optical laminate with adhesive layer] The method for producing the optical laminate with an adhesive layer is not particularly limited, and for example, the following method may be mentioned. Examples include: a method of manufacturing a laminate [release-treated substrate / adhesive layer / optical film] using the same method as the method described in the above-mentioned method for forming the adhesive layer, or a method of forming a laminate [release-treated substrate / adhesive layer / release-treated substrate] using the same method as the method described in the above-mentioned method for forming the adhesive layer, peeling off one side of the release-treated substrate from the laminate and attaching an optical film to the exposed adhesive layer. The optical laminate with the present adhesive layer thus obtained can be processed into a desired shape as needed. Example
[0098] Hereinafter, one embodiment of the present invention will be described in more detail based on examples, but the present invention is not limited to these examples.
[0099] <Weight average molecular weight (Mw), number average molecular weight (Mn), molecular weight distribution (Mw / Mn)> The weight average molecular weight (Mw), number average molecular weight (Mn) and molecular weight distribution (Mw / Mn) of each polymer were analyzed by gel permeation chromatography (GPC) under the following conditions and calculated in terms of polystyrene. · Apparatus: GPC-8220 (manufactured by Tosoh Corporation) Chromatographic column: TSKgel G7000H XL / 7.8mmID1×1+TSKgel GMH XL / 7.8mmID×2pcs+TSKgel G2500H XL / 7.8mmID×1 piece (all manufactured by Tosoh Corporation) Medium: Tetrahydrofuran Flow rate: 1.0mL / min Concentration: 1.5 mg / mL Injection volume: 300μL Column temperature: 40°C
[0100] [Synthesis example 1] In a reaction apparatus equipped with a stirrer, a reflux cooler, a thermometer, and a nitrogen inlet pipe, 99.99 parts by mass of 2-methoxyethyl acrylate (MEA), 0.01 parts by mass of 4-hydroxybutyl acrylate (4-HBA), and 100 parts by mass of ethyl acetate were added, and the temperature was raised to 70°C while introducing nitrogen. Next, 0.05 parts by mass of 2,2'-azobisisobutyronitrile (hereinafter also referred to as "AIBN") was added, and a polymerization reaction was carried out at 75 to 76°C for 4 hours under a nitrogen atmosphere to synthesize a copolymer a1. After the reaction was completed, the reaction solution was diluted with ethyl acetate to a copolymer concentration of 15% by mass to prepare a polymer solution. The Mw of the obtained copolymer a1 was 1.6 million, and the molecular weight distribution (Mw / Mn) was 3.5.
[0101] [Synthesis example 2] Copolymer a2 was synthesized in the same manner as in Synthesis Example 1 except that the types and amounts of the monomers used were changed as shown in Table 1. The Mw of the obtained copolymer a2 was 1.6 million and the molecular weight distribution (Mw / Mn) was 3.5.
[0102] [Synthesis example 3] Copolymer Ca1 was synthesized in the same manner as in Synthesis Example 1 except that the types and amounts of the monomers used were changed as shown in Table 1. The Mw of the obtained copolymer Ca1 was 1.6 million and the molecular weight distribution (Mw / Mn) was 4.5.
[0103] [Synthesis Example 4] Copolymer Ca2 was synthesized in the same manner as in Synthesis Example 1 except that the types and amounts of monomers used were changed as shown in Table 1. The Mw of the obtained copolymer Ca2 was 1.55 million, and the molecular weight distribution (Mw / Mn) was 4.5.
[0104] [Synthesis example 5] Copolymer a3 was synthesized in the same manner as in Synthesis Example 1 except that the types and amounts of the monomers used were changed as shown in Table 1. The Mw of the obtained copolymer a3 was 1.7 million and the molecular weight distribution (Mw / Mn) was 4.0.
[0105] [Synthesis example 6] Copolymer a4 was synthesized in the same manner as in Synthesis Example 1 except that the types and amounts of the monomers used were changed to those shown in Table 1 and the amount of AIBN used was changed to 0.08 parts by mass. The Mw of the obtained copolymer a4 was 1.2 million and the molecular weight distribution (Mw / Mn) was 5.0.
[0106] [Synthesis Example 7] Copolymer Ca3 was synthesized in the same manner as in Synthesis Example 1 except that the types and amounts of the monomers used were changed to those shown in Table 1 and the amount of AIBN used was changed to 0.08 parts by mass. The Mw of the obtained copolymer Ca3 was 1.2 million and the molecular weight distribution (Mw / Mn) was 5.0.
[0107] Table 1
[0108] The meanings of the symbols of the monomers in Table 1 are as follows. ·MEA: 2-Methoxyethyl acrylate BA: n-butyl acrylate ·2-HEA: 2-Hydroxyethyl acrylate 4-HBA: 4-Hydroxybutyl acrylate AA: Acrylic acid
[0109] [Example 1] [Preparation of Adhesive Composition] To the polymer solution of copolymer a1 obtained in Synthesis Example 1, 11 parts by mass of isocyanurate of xylylene diisocyanate (D-131N, produced by Mitsui Chemicals, Inc.) as a cross-linking agent was added based on the solid content to 100 parts by mass of copolymer a1, and further 0.2 parts by mass of a silane coupling agent (A-50, produced by Soken Chemical Co., Ltd.) was added based on the solid content to obtain an adhesive composition A.
[0110] (Gel fraction) <Preparation of Adhesive Sheet for Gel Fraction Measurement> After removing bubbles from the obtained adhesive composition A, the degassed adhesive composition A was applied to a release-treated polyethylene terephthalate film (PET film) with a doctor blade, and dried at 90° C. for 3 minutes to form a coating film with a dry film thickness of 10 μm. A release-treated PET film was further attached to the surface of the coating film opposite to the PET film, and the coating film was cured by standing for 7 days under a 23° C. / 50% RH environment to prepare an adhesive sheet having an adhesive layer with a thickness of 10 μm sandwiched between two PET films.
[0111] <Measurement of gel fraction> About 0.1 g of the adhesive layer was collected from the obtained adhesive sheet and placed in a sample bottle. 30 mL of ethyl acetate was added and shaken for 4 hours. The contents of the sample bottle were filtered through a 200-mesh stainless steel mesh. The residue on the mesh was dried at 100° C. for 2 hours and the dry mass was measured. The gel fraction of the adhesive layer was calculated by the following formula. The results are shown in Table 2. Gel fraction (mass %) = (dry mass / adhesive layer collected mass) × 100 (mass %)
[0112] 〔Adhesion〕 <Preparation of Polarizing Film with Adhesive Layer> After removing bubbles from the obtained adhesive composition A, the defoamed adhesive composition A was applied to the PET film subjected to the peeling treatment with a doctor blade, and dried at 90° C. for 3 minutes to obtain a sheet having a coating film with a dry film thickness of 10 μm. The coated surface of the sheet was attached to a polarizing film (composition: triacetyl cellulose / polyvinyl alcohol / triacetyl cellulose) with a thickness of 94 μm, and cured by standing for 7 days under the conditions of 23° C. / 50% RH to prepare a polarizing film with an adhesive layer having a PET film, an adhesive layer with a thickness of 10 μm, and a polarizing film.
[0113] <Measurement of Adhesion Strength> The obtained polarizing film with an adhesive layer was cut into a 25 mm wide strip to prepare a test piece. The PET film was peeled off from the prepared test piece, and the exposed adhesive layer was pasted on a glass plate and pressed with a 2 kg roller. Next, it was treated in an autoclave at 50°C and 5 atm for 20 minutes, and then allowed to stand for 1 hour in an environment of 23°C / 50% RH. Then, one end of the polarizing film was stretched at a stretching rate of 300 mm / min in a direction of 180° relative to the adhesive surface, and the adhesive force (peel strength) required for peeling was measured. The results are shown in Table 2.
[0114] [High temperature durability] 〈Preparation of samples for high temperature durability evaluation〉 The polarizing film with adhesive layer was cut into 150 mm × 250 mm, the PET film was peeled off, and it was pasted on a glass plate with a thickness of 1.1 mm and pressed with a 2 kg roller. Then, it was autoclaved at 50°C and 5 atm for 20 minutes and placed in an environment of 23°C / 50% RH for 24 hours to prepare an evaluation sample.
[0115] 〈Evaluation of high temperature durability〉 The prepared evaluation samples were left to stand for 500 hours in an environment of 115°C. Then, they were taken out and left to stand for 24 hours in an environment of 23°C / 50%RH, and the appearance was visually evaluated according to the following criteria. The results are shown in Table 2. Among them, the evaluation results of ○ or △ were evaluated as having high-temperature durability suitable for use in optical components. (Evaluation Criteria) ○: No peeling occurred. △: No peeling occurred, but slight foaming occurred. ×: Peeling occurred.
[0116] 〔Yellowing property〕 After removing bubbles from the obtained adhesive composition A, the defoamed adhesive composition A was applied to the PET film subjected to the peeling treatment with a doctor blade, and dried at 90°C for 3 minutes to form a coating film with a dry film thickness of 20 μm. A PET film subjected to the peeling treatment was further pasted on the surface of the coating film opposite to the pasting surface of the above-mentioned PET film, and the coating film was left to stand for 7 days under a 23°C / 50%RH environment for curing to prepare an adhesive sheet having an adhesive layer with a thickness of 20 μm sandwiched between two PET films. Then, one PET film of the prepared adhesive sheet was peeled off and pasted on a glass plate, and the other PET film was also peeled off and only the adhesive layer was pasted on the glass plate, which was used as a sample for yellowing evaluation. The yellowness (YI0) of the obtained evaluation sample [hereinafter also referred to as "initial value YI0"]. ] was measured using a spectrophotometer ("TZ7700" manufactured by Nippon Denshoku Industries Co., Ltd.) in accordance with JIS K 7373:2006. Then, the evaluation sample was left to stand for 500 hours in a high temperature environment of 115°C, and the yellowness (YI) of the evaluation sample after standing in the high temperature environment [hereinafter also referred to as "YI after durability"] was measured in the same manner as the initial value YI0. Furthermore, the yellowing value (ΔYI) was calculated using YI0 and YI according to the following formula. The results are shown in Table 2. ΔYI=(YI of the adhesive layer after high temperature durability)-(YI0 of the adhesive layer before high temperature durability)
[0117] [Examples 2 and 3] Adhesive strength and high temperature durability were evaluated in the same manner as in Example 1 except that the adhesive composition A prepared in Example 1 was used and the thickness of the adhesive layer of the polarizing film with an adhesive layer used in the adhesive strength and high temperature durability evaluation test was changed to that shown in Table 2. The results are shown in Table 2. However, regarding the gel fraction, yellowness and yellowing value, since the adhesive composition A was used in both Examples 2 and 3, the values were the same as those in Example 1.
[0118] [Examples 4 to 6, Comparative Examples 1 to 7] An adhesive composition was prepared in the same manner as in Example 1 except that the compounding composition was changed to that described in Table 2. In Table 2, the numerical values of each crosslinking agent and silane coupling agent represent the addition amount (parts by mass) of these components relative to 100 parts by mass of the copolymer compounded in the adhesive composition. Using the obtained adhesive composition, an adhesive sheet was prepared and the gel fraction was measured in the same manner as in Example 1. Furthermore, a polarizing film with an adhesive layer was prepared in the same manner as in Example 1, except that the obtained adhesive composition was used and the thickness of the adhesive layer of the polarizing film with an adhesive layer was changed to that described in Table 2, and the adhesive force and high-temperature durability of the polarizing film with an adhesive layer were evaluated in the same manner as in Example 1. In addition, the yellowness (YI0, YI) and the yellowing value (ΔYI) were determined in the same manner as in Example 1 using the obtained adhesive composition. Among them, the adhesive composition prepared in Comparative Example 6 gelled and a polarizing film with an adhesive layer could not be produced. In addition, since the polarizing film with an adhesive layer produced in Comparative Example 7 was whitened, it is indicated as “whitened” in Table 2.
[0119] Table 2
[0120] The symbols of the crosslinking agent and the silane coupling agent in Table 2 have the following meanings. ·D-131N: Isocyanurate of xylylene diisocyanate (manufactured by Mitsui Chemicals, Inc.) TD-75: Trimethylolpropane adduct of xylylene diisocyanate (produced by Soken Chemical Co., Ltd.) ·L-45: Trimethylolpropane adduct of toluene diisocyanate (produced by Soken Chemical Co., Ltd.) ·E-5CM: Epoxy crosslinking agent (produced by Soken Chemical Co., Ltd.) ·A-50: Silane coupling agent (produced by Soken Chemical Co., Ltd.)
[0121] In Examples 1 to 6, an adhesive composition was obtained which was capable of forming an adhesive layer having excellent high-temperature durability despite being a thin film and which was less likely to yellow or whiten. In contrast, the yellowing values ΔYI were large in Comparative Examples 1, 4, and 5, indicating that yellowing was not sufficiently suppressed. In Comparative Examples 2 to 4, the adhesive layer peeled off after being left to stand at 115° C. for 500 hours, indicating that the high temperature durability was insufficient.
Claims
1. An adhesive composition comprising a (meth)acrylic copolymer and an isocyanate crosslinking agent, The (meth)acrylic copolymer is a copolymer of a monomer mixture containing 20% by mass or more of a (meth)acrylic monomer having an alkylene oxide group. The isocyanate crosslinking agent has 3 or more isocyanate groups derived from a xylylene diisocyanate compound, and the content of the isocyanate crosslinking agent is greater than 2 parts by mass and less than 30 parts by mass based on 100 parts by mass of the (meth)acrylic copolymer.
2. The adhesive composition according to claim 1, wherein The (meth)acrylic copolymer is a copolymer of a monomer mixture containing 50% by mass or more of a (meth)acrylic monomer having an alkylene oxide group.
3. The adhesive composition according to claim 1 or 2, wherein The (meth)acrylic copolymer has a content of a structural unit derived from an acidic group-containing monomer of less than 1% by mass.
4. The adhesive composition according to claim 1 or 2, wherein The isocyanate cross-linking agent is an isocyanurate.
5. The adhesive composition according to claim 1 or 2, wherein The (meth)acrylic copolymer has a molecular weight distribution Mw / Mn, which is a ratio of a polystyrene-equivalent weight average molecular weight Mw to a number average molecular weight Mn measured by gel permeation chromatography, of greater than 3.
6. The adhesive composition according to claim 1 or 2, wherein It is used in optical components. 7 . An optical laminate with an adhesive layer, comprising an adhesive layer formed from the adhesive composition according to claim 1 or 2 and an optical film.
8. An optical laminate with an adhesive layer, comprising an adhesive layer formed from the adhesive composition according to claim 1 or 2 and an optical film, The adhesive layer has a thickness of 20 μm or less.
9. An optical laminate with an adhesive layer, comprising an adhesive layer formed from the adhesive composition according to claim 1 or 2 and an optical film, The adhesive layer has a yellowing value ΔYI, which is a difference in yellowness calculated in accordance with JIS K7373:2006, of 2.0 or less before and after being left to stand in an environment of 115° C. for 500 hours.
Citation Information
Patent Citations
Pressure-sensitive adhesive agent and optical film
JP2010159346A
Self-adhesive composition for polarizing plate and polarizing plate using the same
JP2010196003A